Pengetahuan, Sikap, dan Tindakan Murid Pondok Pesantren Dr. M. Natsir Alahan Panjang Tentang Skabies - Satya Wydya Yenny; Rendra Darmasatria; Resya I Noer; Virnanda Trisnorizki Saputra; Dwi Sabtika Julia; Netty Suharti (Warta Pengabdian Andalas, 2023)
Scabies is a skin disease caused by infestation and sensitization to Sarcoptes scabei hominis. The incidence of scabies at the Islamic boarding school Dr M. Natsir Alahan Panjang is as much as 17.5%. The purpose of this activity was to describe the students' knowledge before and after counselling and the attitudes and behaviour of the students in dealing with scabies. The method was observational analytic with a cross-sectional approach with 216 students who met the inclusion and exclusion criteria at the school. Based on the data, 146 respondents met the inclusion criteria, with respondents 16 years old and 29 respondents (19.9%) ranging in age from 12 to 21 years. The education level of the majority came from senior high school, with as many as 89 respondents (56.2%). Respondents did not understand about scabies with 115 (78,8%) but already had good knowledge about scabies with 135 (92,6%). There was an increase in the respondents' knowledge where initially, the respondents' knowledge before counselling had a percentage of 96,6% to 98% after counselling. In the attitude and behaviour aspects of the respondents, there was also an increase after counselling was carried out. There was a significant difference in knowledge between before and after counselling.